PROBLEMATICS OF LGBT ACCORDING TO MAQASID AL-SYARIAH WITH HIFDZ NASHL - Indah; Nafiah; Almas Syafa; Siti Fatmala; Musyaffa Amin Ash Shabah (Universitas Islam Negeri Mataram, 2023)
This research reviews LGBT issues which are increasingly being discussed because everything seems to be something normal. This is due to the increasing access to globalization, reaching 8,013 cases in Bogor district where LGBT marriages are taking place. Thus this study analyzes the problems related to LGBT marriage to hifdz nashl. This research also uses qualitative methods with literature review, is library research which is literature review research by collecting various sources from both primary and secondary sources and uses library research methodology in analyzing secondary legal materials in the form of reading, analyzing, and collecting data from library research The results of the research are related to Islamic views which include the Qur'an and hadith as well as the consensus of the scholars who say that marriage is an act that is unlawful because of the impact of the LGBT community. In this case, the problems of LGBT marriages can have a major impact on hifdz nashl, as well as discussing how marriage in Islam should be carried out by a man and a woman and perform consent qobul between the man and the marriage guardian with two witnesses. So, when a man marries a man or vice versa it will be equated with adultery which is unlawful.